A retrospective study of laparoscopic surgery for small bowel obstruction. (April 2017) - Otani, Kensuke; Ishihara, Soichiro; Nozawa, Hiroaki; Kawai, Kazushige; Hata, Keisuke; Kiyomatsu, Tomomichi; Tanaka, Toshiaki; Nishikawa, Takeshi; Yasuda, Koji; Sasaki, Kazuhito; Murono, Koji; Watanabe, Toshiaki
Abstract: Background: Open laparotomy is widely accepted as the standard surgical treatment for small bowel obstruction (SBO). However, laparoscopic surgery has recently become a treatment option. There is no consensus on the appropriate settings for the laparoscopic treatment of SBO. The purpose of this study is to evaluate the outcomes of laparoscopic surgery for SBO. Patients and methods: From January 2012 to May 2016, 48 consecutive patients underwent surgical treatment for SBO in our department. We retrospectively reviewed these cases and compared the features and the outcomes between laparoscopic and open surgery. Results: Thirty-four and 14 patients underwent open surgery and laparoscopic surgery, respectively. Four of the laparoscopic cases (28.6%) were converted to open surgery. Laparoscopic surgery tended to be associated with a shorter operative time than open surgery (p = 0.066). The first postoperative oral intake was significantly earlier in patients who underwent laparoscopic surgery (p = 0.044). The duration of hospitalization after surgery and the rates of postoperative complications did not differ to a statistically significant extent. Laparoscopic treatment was accomplished in 7 out of 8 cases (87.5%) with SBO due to band occlusion. Conclusion: Laparoscopic surgery for SBO is less invasive than open surgery and is equally feasible in selected patients. SBO due to band occlusion may be a preferable indication for laparoscopic surgery. In order to confirm the safety of laparoscopic treatment, and to clarify the appropriate settings for laparoscopic surgery for SBO, it will be necessary to perform further studies in a larger population and with a long follow-up period. Highlights: Surgical treatment for small bowel obstruction in 48 patients were retrospectively reviewed. Laparoscopic surgery was performed in 14 patients, and 4 cases were converted to open surgery. Laparoscopic surgery is less invasive than open surgery and is equally feasible in selected patients. Band occlusion may be a preferable indication to laparoscopic surgery.